Prenatal yoga exercise improves sleep quality in the third trimester of pregnant women - Hajratul Azward; Sri Ramadhany; Nugraha Pelupessy; Andi Nilawati Usman; Farida Tandi Bara (Elsevier, 2021)
Objective: This study aims to determine the effect of prenatal yoga exercises on sleep quality in third-trimester pregnant women. Methods: It was a quasi-experimental (Nonequivalent Control Group Design). The study was conducted at the Ma'rang Community Health Center in Pangkajene and Kepulauan District from January to March 2020. The sample in this study was 60 pregnant women with gestational age 28 weeks divided into two groups, namely 30 control groups, namely pregnant women who visited routine antenatal check-ups as usual, and 30 people in the intervention group were given prenatal yoga exercises four times in two weeks selected based on purposive sampling techniques. Data analysis using the Wilcoxon test (p < 0.05). Results: Statistical test results showed that in the control group (p-value 0.001 < 0.05) and intervention (p-value 0.001 < 0.05), there were significant differences in sleep quality before and after the intervention was given. Conclusion: Prenatal yoga exercises improve the sleep quality of third-trimester pregnant women.